Music Teachers Perceptions of Creativity: A Preliminary Investigation. Issue 4 (2nd October 2019) - Kladder, Jonathan; Lee, William
Abstract : Music teachers embrace perceptions of creativity across a diversity of music teaching and learning contexts. A review of literature revealed limited research has investigated these perceptions. The purpose of this preliminary investigation was to examine music teacher's perceptions of creativity, including how it is defined, supported in the classroom, and how creative students are perceived. A researcher-developed questionnaire was built from similar investigations across different domains. The questionnaire was distributed electronically to a sample of music teachers in the southeastern region of the United States ( n =  164). Respondents defined creativity as a novel or new idea resulting in a formalized product and believed that creative students are risker-takers, persistent, and often think outside the box. The classroom environment was perceived as important to the creative processes and providing space for collaboration enhanced creative thinking. Implications for the field of music education and further research are discussed in conclusion.